2021
DOI: 10.1021/acs.orglett.1c00716
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Domino Heck/Sulfination: Synthesis of Sulfonylated Hetero- and Carbocyclic Scaffolds Using DABCO–Bis(sulfur dioxide)

Abstract: The synthesis of a broad variety of hetero- and carbocyclic scaffolds via a Pd-catalyzed domino Heck/SO2 insertion reaction is reported. This reaction utilizes DABSO, a safe and easy-to-handle alternative to SO2 gas. The reaction proceeds through a sulfinate intermediate, which can act as a lynchpin for the in situ generation of sulfones, sulfonamides, and sulfonyl fluorides. Good yields and scalability are demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…was adjusted to 3.0, 4.0, 5.0 and 7.0 equiv. respectively (Table 1, entries [15][16][17][18]. Neither increasing the temperature to 125 °C nor decreasing it to 80 °C or 95 °C would help to enhance the product yield (Table 1, entries 19-21).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…was adjusted to 3.0, 4.0, 5.0 and 7.0 equiv. respectively (Table 1, entries [15][16][17][18]. Neither increasing the temperature to 125 °C nor decreasing it to 80 °C or 95 °C would help to enhance the product yield (Table 1, entries 19-21).…”
Section: Resultsmentioning
confidence: 99%
“…Oxidative addition of Pd(0) catalyst into 1 a generated aryl palladium species A, which would subsequently undergo an intramolecular cyclization to produce alkyl palladium species B. [18] Then, the insertion of SO 2 into intermediate B made sulfinate palladium salt C [15] which would exist in equilibrium with alkyl sulfonyl palladium complex D. In the presence of base, amines 2 a would have anion exchange with complex D to generate intermediate E. [19] Finally, reductive elimination of intermediate E would allow the formation of the desired sulfonamide 3 a and the regeneration of Pd(0) species for the next catalytic cycle.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…40 Lautens and co-workers showed that cyclic sulfonated products could be prepared through a Pd-catalyzed intramolecular Heck reaction followed by a Pd-catalyzed reaction with DABSO to prepare a sulfinate, from which sulfones, sulfonamides and sulfonyl fluorides were obtained. 41…”
Section: Metal-catalyzed Reactionsmentioning
confidence: 99%
“…40 Lautens and co-workers showed that cyclic sulfonated products could be prepared through a Pd-catalyzed intramolecular Heck reaction followed by a Pd-catalyzed reaction with DABSO to prepare a sulfinate, from which sulfones, sulfonamides and sulfonyl fluorides were obtained. 41 Scheme 11 Pd-catalyzed synthesis of sulfonyl derivatives from aryl halides Sulfonyl fluorides are valuable products. They are hydrolytically stable, but under the correct conditions can undergo sulfur(VI) fluoride exchange (SuFEx) 'click chemistry' reactions.…”
Section: Short Review Synthesismentioning
confidence: 99%